Assessment of water quality in the Mosca River, Junín, using the Water Quality Index (WQI) and its impact on water resource use (Research, Society and Development, 2025)
The investigation aims to evaluate the water quality of the Mosca River, located in Junín, Ecuador, through the application of the Water Quality Index (ICA-NSF), with the aim of determining the degree of contamination and its incidence in the use of the water resource. This river constitutes an essential source for human consumption, agriculture and recreational activities; However, its quality is compromised by wastewater discharges and the use of agrochemicals. Samples were collected at five sampling points throughout the basin, analyzing physicochemical parameters such as temperature, pH, oxygen dilution (DO) and fecal coliforms. The values ​​obtained from ICA-NSF (66.06, 66.19, 65.96, 66.15 and 56.39) classify the water quality as regular, which means that it is acceptable for aquatic life, even with limitations regarding biodiversity. If the temperature and oxygen levels are high, high levels of fecal coliforms show considerable contamination. These results demonstrate the need to implement mitigation measures that contribute to reducing contamination and ensuring the protection of this fundamental water resource.